Halalan Toyyiban: Theory and Implementation of Food Products Consumers - Novi Yanti Sandra Dewi; Ahadiah Agustina (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
For a Muslim consuming food is not only good taste, but also must meet the criteria of halalan thayyiban. Halal food is not necessarily thayyiban, because halal food at the time of processing may be given additional ingredients that are not halal. Consumers of food products should have spiritual awarenes (spiritual awareness) related to food products that they consume, especially Muslim consumers. Consuming halal food thayyiban is an order from Allah SWT, where this halal food product thayyiban has several characteristics that the food is classified as halal food, contains adequate nutrition and balanced, proportional, and safe. The purpose of this study is to examine more deeply about the theory of halalan thayyiban and the implementation of consumers of food products against the theory of halalan thayyiban, with the method used is qualitative method.